2022
DOI: 10.3390/cells11223606
|View full text |Cite
|
Sign up to set email alerts
|

LTB4R Promotes the Occurrence and Progression of Clear Cell Renal Cell Carcinoma (ccRCC) by Regulating the AKT/mTOR Signaling Pathway

Abstract: ccRCC is highly immunogenic, yet its underlying immune-related molecular mechanisms are unknown. Leukotriene B4 Receptor 1 (LTB4R), a novel immune-related gene associated in our previous research with the prognosis of ccRCC patients, has been found in many cancers; however, its potential mechanism in renal clear carcinoma is unclear. This study was conducted to investigate LTB4R’s action mechanism in renal clear cell carcinoma. First, a CCK8 assay was performed to verify LTB4R’s effect on the proliferation via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…As expected, upregulated LTB4R is associated with poor prognoses in patients with TNBC. Previously, for another tumor type, e.g., clear cell renal cell carcinoma, Zhang et al [32] presented high LTB4R expression as an important cancer marker and possibly a highly specific target associated with a poor prognosis due to the promotion of cancer cell proliferation, migration, development, and progression via the Akt/mTOR pathway. Pan-cancer bioinformatic analysis revealed that higher LTB4R expression was associated with poor relapse-free survival (RFS), poor OS, and poor distant metastasis-free survival (DMFS) in breast cancer datasets without segregation into molecular subtypes [33].…”
Section: Discussionmentioning
confidence: 99%
“…As expected, upregulated LTB4R is associated with poor prognoses in patients with TNBC. Previously, for another tumor type, e.g., clear cell renal cell carcinoma, Zhang et al [32] presented high LTB4R expression as an important cancer marker and possibly a highly specific target associated with a poor prognosis due to the promotion of cancer cell proliferation, migration, development, and progression via the Akt/mTOR pathway. Pan-cancer bioinformatic analysis revealed that higher LTB4R expression was associated with poor relapse-free survival (RFS), poor OS, and poor distant metastasis-free survival (DMFS) in breast cancer datasets without segregation into molecular subtypes [33].…”
Section: Discussionmentioning
confidence: 99%
“…Feng G et al found that miR-30e could inhibit the proliferation of liver cancer cells by targeting P4HA1 16 . Vitro and vivo studies con rm that P4HA2 can regulate PI3K/Akt/mTOR signaling pathway to promote the occurrence and development of liver cancer 17 .Similarly to P4HA2, P4HA3 can mediate clear cell renal cell carcinoma progression by regulating the PI3K/AKT/GSK3β pathway 18 . However, the expression and function of P4Hs in HNSC is not clear, and the clinical value of P4Hs in HNSC remain largely unknown.…”
Section: Introductionmentioning
confidence: 92%
“…A very recent study showed that LTB 4 R overexpression promoted proliferation and inhibited apoptosis of ccRCC cells by stimulating the AKT/mTOR signaling pathway [ 169 ]. Moreover, migration and invasion were inhibited when LTB 4 R was depleted [ 169 ].…”
Section: Eicosanoids In Renal Cancermentioning
confidence: 99%
“…A very recent study showed that LTB 4 R overexpression promoted proliferation and inhibited apoptosis of ccRCC cells by stimulating the AKT/mTOR signaling pathway [ 169 ]. Moreover, migration and invasion were inhibited when LTB 4 R was depleted [ 169 ]. According to the TCGA database, LTB 4 R was overexpressed in ccRCC samples compared to normal samples and patients with higher LTB 4 R expressions showed significantly poorer overall survival than patients with lower LTB 4 R [ 169 ].…”
Section: Eicosanoids In Renal Cancermentioning
confidence: 99%
See 1 more Smart Citation